1996
DOI: 10.1093/jn/126.9.2130
|View full text |Cite
|
Sign up to set email alerts
|

Normal Subjects Consuming Physiological Levels of 18:3(n-3) and 20:5(n-3) from Flaxseed or Fish Oils Have Characteristic Differences in Plasma Lipid and Lipoprotein Fatty Acid Levels

Abstract: The study assessed the effect of low doses of fatty acids from fish or flaxseed oil on plasma lipid concentrations in normal humans consuming diets with either high (0.87, n = 11) or low (0.48, n = 15) dietary polyunsaturated/saturated fatty acid (P/S) ratios. The dose of (n-3) fatty acids reflected an (n-3) intake that could easily be attained by selection of foods in a normal diet. The individuals were initially supplemented with olive oil [35 mg 18:1/(kg body weight.d)], and then were randomly assigned to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
2
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 40 publications
0
47
2
3
Order By: Relevance
“…This ®nding is consistent with that of Abbey et al (1994) who found that walnuts did not increase plasma eicosapentaenoic acid when compared to a reference diet with a PaS ratio of 0.4-similar to our low fat diet-but is in contrast to that of Sabate et al (1993). The n-6an-3 polyunsaturated fatty acid ratio in walnuts is roughly 5:1 (Quigley et al, 1995), whereas in canola and¯axseed oils, also advocated for their alpha linolenic acid content, the ratios are roughly 2:1 (Quigley et al, 1995) and 1:4 (Layne et al, 1996), respectively. Chan et al (1993) and others (Abbey et al, 1994;Layne et al, 1996;Lichtenstein et al, 1993, Valsta et al, 1996 have reported that when using alpha linolenic acid rich oils if the n-6an-3 ratio in the overall diet is high (namely b 5) an increase in plasma alpha linolenic acid can occur, but there is little, if any, increase in eicosapentaenoic acid content of plasma lipids above that of a standard reference diet.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This ®nding is consistent with that of Abbey et al (1994) who found that walnuts did not increase plasma eicosapentaenoic acid when compared to a reference diet with a PaS ratio of 0.4-similar to our low fat diet-but is in contrast to that of Sabate et al (1993). The n-6an-3 polyunsaturated fatty acid ratio in walnuts is roughly 5:1 (Quigley et al, 1995), whereas in canola and¯axseed oils, also advocated for their alpha linolenic acid content, the ratios are roughly 2:1 (Quigley et al, 1995) and 1:4 (Layne et al, 1996), respectively. Chan et al (1993) and others (Abbey et al, 1994;Layne et al, 1996;Lichtenstein et al, 1993, Valsta et al, 1996 have reported that when using alpha linolenic acid rich oils if the n-6an-3 ratio in the overall diet is high (namely b 5) an increase in plasma alpha linolenic acid can occur, but there is little, if any, increase in eicosapentaenoic acid content of plasma lipids above that of a standard reference diet.…”
Section: Discussionmentioning
confidence: 56%
“…The n-6an-3 polyunsaturated fatty acid ratio in walnuts is roughly 5:1 (Quigley et al, 1995), whereas in canola and¯axseed oils, also advocated for their alpha linolenic acid content, the ratios are roughly 2:1 (Quigley et al, 1995) and 1:4 (Layne et al, 1996), respectively. Chan et al (1993) and others (Abbey et al, 1994;Layne et al, 1996;Lichtenstein et al, 1993, Valsta et al, 1996 have reported that when using alpha linolenic acid rich oils if the n-6an-3 ratio in the overall diet is high (namely b 5) an increase in plasma alpha linolenic acid can occur, but there is little, if any, increase in eicosapentaenoic acid content of plasma lipids above that of a standard reference diet. Increasing eicosapentaenoic acid levels by consuming alpha linolenic acid-rich oils appears to require a low n-6an-3 ratio (namely`3) in the overall diet as well as a high intake of alpha linolenic acid (Chan et al, 1993;Mantzioris et al, 1994Mantzioris et al, , 1995, not easily achieved by supplementing a low fat diet with walnuts, as in the present experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Olive oil was selected as the placebo, as it was not expected to alter plasma lipids or essential fatty acid metabolism (Thien et al, 1993;Yaqoob et al, 2000). The fatty acid composition of the fish oil and placebo capsules was determined using gas liquid chromatography (Layne et al, 1996) (Table 1). All investigators and health care workers were blinded to the treatment received throughout the trial.…”
Section: Subjectsmentioning
confidence: 99%
“…Briefly, plasma (100 ml) fatty acids were extracted using chloroform/methanol and serum PL isolated on G-plates (Layne et al, 1996). For quantitative analysis, C17:0 standard was added to the scraped serum PL (10 mg of C17:0) followed by direct methylation.…”
Section: Clinicalmentioning
confidence: 99%
“…In order to examine whether the perilla-oil diet (PD) has less preferable food properties than the LD as compared to the FD, we undertook study 2, to compare the preference for the LD and the PD when rats were placed on a selfselection regimen of both diets after being fed the LD or the PD during the growth period. Further, although EPA and DHA have been shown to decrease blood lipid concentrations, the effects of ALA on blood lipids are equivocal (28)(29)(30). The present study also compared the effects of the precursor n -3 PUFA (ALA) contained in perilla oil on blood lipid levels with those of EPA ϩ DHA containing fish oil.…”
mentioning
confidence: 93%